Igreja para a comunidade de Nossa Senhora do Perpetuo Socorro - SENA, Samantha Moy de (2023)
The proposal of a new Church of Nossa Senhora do Perpétuo Socorro is an element that contributes to the realization of the proposals of what is intended about an evangelization combined with the welcome and support to the Catholic community originally proposed by the Second Vatican Council and reaffirmed. In document 100, communities of communities of the National Council of Bishops of Brazil. Where the opening of the church to the reality that afflicts the community is accompanied and welcomed through social care services, allowing socializing without any kind of exclusion and carried out with the support of the community itself. The choice of theme was due to the need to provide for the community of Nossa Senhora do Perpétuo Socorro to have a physical church that met the needs of the local Catholic community in dimensions and services. With the precedent analysis studies, it was possible to extract elements necessary for the elaboration of the project proposal of the church.